Perancangan Sistem Informasi Penjadwalan Laboratorium Pendidikan Informatika Universitas PGRI Sumatera Barat - Giawa, Erwin Sofyan Putri; Mary, Thomson; Samudra, Ami Anggraini (Universitas PGRI Sumatera Barat, 2022)
The preparation and writing of the practicum lecture schedule in the Informatics Education computer laboratory has not been optimal. In addition, the laboratory loan process has not been efficient in terms of time, because lecturers and students have to contact and come directly to the laboratory. The purpose of this study was to design and test a laboratory scheduling information system for the informatics education study program at Universitas PGRI Sumatera Barat using the Software Development Life Cycle (SDLC) method. This research resulted in an information system that can help labor technicians, lecturers, students and related stakeholders. The results of beta testing research on expert validation obtained an average validation of 87.4% with very good information and the user assessment questionnaire obtained an average value of 89.8% with very good information.